PERANAN CUMI-CUMI BAGI KESEHATAN - Diah Anggraini Wulandari (OSEANA, 2018)
THE BENEFITS AND ROLE OF SQUID FOR HEALTH. Squids are rich in protein with a protein content 15-20%. Squids containing macro and micro minerals such as sodium, potassium, phosphorus, calcium, magnesium and selenium, besides that squid also comprise essential amino acids such as tryptophan, threonine, methionine, lysine, leucine, isoleucine, valine, phenylalanine, and non-essential amino acids such as glutamic acid, aspartic acid, tyrosine, cysteine, serine, proline, glycine, arginine and histidine. Squid ink contain alkaloids that potential as anti-inflammatory, antihypertensive, anti-diabetic, anti-microbial and anti-malaria agents. The benefit of Squids in the food industry are an enhancer of flavor and an artificial leather constituent in the biomedical field.